PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3) DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DIVISI PRODUKSI PT. PRIMA KOMPONEN INDONESIA - Sandi Puji Juliandika; Hira Maulida (Journal of Research and Publication Innovation, 2025)
This research aims to analyze the influence of occupational safety and health (K3) and work discipline on employee performance in the production division of PT Prima Components Indonesia. The research method used in this research is a quantitative method. The population in this study were all employees of the production division of PT Prima Component Indonesia as many as 104 people. The sample used was the Slovin sample so there were 83 people. The data analysis method uses simple linear regression, multiple, correlation coefficient, coefficient of determination, partial t test and simultaneous F test. The results of this research show that: (1) There is a positive and significant influence between Occupational Safety and Health (K3) (X1) on Performance (Y) in the Production Division of PT  Prima Componenten Indonesia, this can be proven from the tcount value of 3.330 > ttable 1.989 with a significance level of 0.000 < 0.05. (2) There is a positive and significant influence between Work Discipline (X2) on Performance (Y) in the Production Division of PT Prima Componenten Indonesia, this can be proven from the tcount value of 7.556> ttable 1.989 with a significance level of 0.000 <0.05. (3) Simultaneously there is a positive and significant influence between Occupational Safety and Health (K3) (X1) and Work Discipline (X2) on Performance (Y) in the Production Division of PT PrimaComponenten Indonesia, this can be proven by obtaining a fcount value of 29,752 > ftable 3.11 with a significance level of 0.000 < 0.05. This research confirms the existence of a positive and significant influence between Occupational Safety and Health (K3), Work Discipline and Employee Performance in the Production Division of PT Prima Componenten Indonesia, which means Ho3 is rejected and Ha3 is accepted.